Natural theology - Scarlett, Brian (Sophia, 2001)
If the theological virtues are supernatural they must be said to be in some sense not natural. This suggests the possibility that they are not only not natural but positively unnatural, in that they postulate either an inhumanly high level of achievement or a divine takeover of human life. The solution proposed draws on Peter Forrest’s work inGod Without the Supernatural: A Defence of Scientific Theism, and suggests a naturalistic account of the virtues in question.